Pengaruh Teknik Audit, Kemampuan Auditor dan Pengalaman Auditor Terhadap Efektivitas Pelaksanaan Prosedur Audit Investigatif dalam Pengungkapan Kecurangan - Cahaya Zulfah; Fathiyah Alifah Fitriyani; Nera Marinda Machdar (Journal of Management and Social Sciences, 2024)
The purpose of this research is to conduct a literature review of previous studies and document various kinds of references on topics and related to the effectiveness of the implementation of investigative audit procedures in disclosing fraud. The method used in this research is a qualitative approach and can also be called a literature study. This research uses secondary data in the form of previous research journals. The results of this study are based on literature in previous research journals by several researchers, it is concluded that audit techniques, auditor ability and auditor experience affect the effectiveness of the implementation of investigative audit procedures in disclosing fraud.